Kinerja Keuangan Bank Syariah Indonesia: Studi Sebelum dan Sesudah Merger - Putri, Larasati Widianto; Ningtyas, Mega Noerman (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2023)
Bank Syariah Indonesia (BSI) was formed by the merger of three state-owned banks: BRI Syariah, BNI Syariah, and Bank Syariah Mandiri. This merger is expected to strengthen the institutions of the Islamic financial industry as well as to increase the Indonesia's Islamic economy in the global arena. Regardless of the benefits and intentions of the merging bank, this activity has impact on its financial performance. this research is conducted to compare the financial performance of BSI before and after the merger. The study approach is descriptive quantitative with ratio analysis, and secondary data is form Monthly Report with an observation period 2020and 2021. This research is indicated s that BSI after the merger is better than before the merger. This is reflected in BSI's growing ability to manage their assets and capital in order to maximize revenue and profitability. However, based on the activity ratio, BSI is not effective and efficient so that they need to do something with their marketing plan in order to increase customer interest.